2023
DOI: 10.1029/2022ja030908
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Latitude Ionospheric Response to a Weak Geomagnetic Activity Event During Solar Minimum

Abstract: The thermospheric and ionospheric responses to geomagnetic disturbances have been studied for several decades. The first type of studies is mostly focusing on one single strong storm (Kp ≥ 5, based on the criteria from NOAA: https://www.swpc.noaa.gov/noaa-scales-explanation) that is mostly generated due to coronal mass ejection. During geomagnetic storms, a tremendous amount of magnetospheric energy is deposited into the ionosphere and thermosphere, which leads to enhancement of Joule heating. Resultingly, enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…The ratios of height‐integrated number density of atomic oxygen (O) to that of molecular nitrogen (N 2 ), namely column O/column N 2 density ratio (∑O/N 2 ), which can be deduced by disk‐viewing optical observations of OI 135.6 nm and Lyman‐Birge‐Hopfield radiances (Meier, 2021; Strickland et al., 1995), has been widely utilized to describe thermospheric neutral composition responses to geomagnetic storms and the storm effects on ionospheric plasma density (e.g., Cai et al., 2020, 2021a, 2021b, 2023; Crowley et al., 2006; Eastes et al., 2020; Lee et al., 2013; Liou et al., 2005; Strickland et al., 1999, 2001; Wang et al., 2021; Yu et al., 2022a, 2022b; Zhai et al., 2023; Zhang et al., 2004). Previous studies demonstrated the evolution and physical processes of ∑O/N 2 during geomagnetic storms, which is briefly summarized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The ratios of height‐integrated number density of atomic oxygen (O) to that of molecular nitrogen (N 2 ), namely column O/column N 2 density ratio (∑O/N 2 ), which can be deduced by disk‐viewing optical observations of OI 135.6 nm and Lyman‐Birge‐Hopfield radiances (Meier, 2021; Strickland et al., 1995), has been widely utilized to describe thermospheric neutral composition responses to geomagnetic storms and the storm effects on ionospheric plasma density (e.g., Cai et al., 2020, 2021a, 2021b, 2023; Crowley et al., 2006; Eastes et al., 2020; Lee et al., 2013; Liou et al., 2005; Strickland et al., 1999, 2001; Wang et al., 2021; Yu et al., 2022a, 2022b; Zhai et al., 2023; Zhang et al., 2004). Previous studies demonstrated the evolution and physical processes of ∑O/N 2 during geomagnetic storms, which is briefly summarized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…ionosphere responses to geomagnetic disturbances (Aa et al, 2022;C. S. Lin et al, 2022;Liou et al, 2005;Lu et al, 2012;Meier et al, 2005;Verkhoglyadova et al, 2017;Zhai, Cai, et al, 2023;Zhai, Tang, et al, 2023; since it reflects the production and loss of the ionospheric F-region plasma (Rishbeth, 1998). Additionally, O and N 2 are two of the major components of the thermosphere, influencing the total mass density of the thermosphere, which is important for monitoring and predicting the drag force of low-Earth-orbiting satellites (Dietrich et al, 2022).…”
mentioning
confidence: 99%
“…In supervising, the principal is expected to be able to compile a supervision program that can provide assistance to teachers to improve teacher professionalism in learning (Zhai et al, 2023). Should, the programs designed by the Principal be able to stimulate changes in teaching for the better.…”
Section: Efforts To Improve Supervisionmentioning
confidence: 99%